HPLC method development for characterisation of the phenolic composition of Cyclopia subternata and C. maculata extracts and chromatographic fingerprint analysis for quality control - Schulze, Alexandra Elizabeth (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScFoodSc)--Stellenbosch University, 2013.